Municipal infectious waste during COVID-19 pandemic: trends, impacts, and management - Iva Yenis Septiariva; I Wayan Koko Suryawan; Ariyanti Sarwono; Bimastyaji Surya Ramadan (International Journal of Public Health Science (IJPHS), 2022)
The coronavirus disease 2019 (COVID-19) shifts the characteristics of municipal waste. This paper aims to provide an overview of trends, impacts, and management during the COVID-19 pandemic globally. The increase in the generation of plastic waste and infectious waste is a new challenge during the COVID-19 pandemic. It was found that the emergence of plastic waste due to the consumption of food delivery becomes an issue in several countries. Despite the increment of plastic waste generation, the mass layoffs contributed to the decrease in the total urban waste generation in general. In addition to plastic waste, a surge of infectious waste from health facilities and household waste originating from residents infected with the SARS-COV-2 virus was observed. This infectious wastewater potentially leads to environmental disturbances to the rivers and oceans. To tackle global environmental concerns, sustainable waste management is required especially in the development of biodegradable personal protective equipment.